Response of faba bean (Viciafaba L.) varieties to lime application in wolaita zone, Southern Ethiopia - Tsige, Bekalu Abebe; Dechassa, Nigussie; Tana, Tamado; Laekemariam, Fanuel; Alemayehu, Yibekal (Revista de Ciências Agroveterinárias, 2023)
Soil acidity and scarcity of faba bean varieties adapted to lower pH soils are major factors that limit faba bean production in Ethiopia. Therefore, an experiment was conducted to find the lime rate and faba bean can improve the yield of the crop. Four rates of lime (0, 2, 4, and 6 t ha–1) and five-faba bean varieties (local, Dosha, Gebelecho, Tumsa, and Bobicho) were used as treatments, which laid out as CRD with six replications. The main and interaction effects of lime rates and varieties significantly (P < 0.05) influenced all growth, yield components, and yield parameters. Nevertheless, root morphological parameters were significantly (P < 0.05) affected by the main effects of the lime rate. Accordingly, the most significant high aboveground biomass of 47.92 g pot–1, and seed yields of (19.16 g pot–1) were obtained in response to the interaction of the Tumsa variety with 3 g pot–1lime rate (2 t ha–1). The lowest aboveground biomass of (32.08 g pot–1) and seed yield of (12.84 g pot–1) were obtained in response to the local variety planted with no lime application. Overall, in terms of seed yield, the Gebelcho and Tumsa varieties performed best by attaining their maximum seed yields in response to the application of 3 g lime pot–1 (2 t ha–1). Thus, 3 g pot–1 (2.0 t ha–1) liming rate with the Gebelcho and Tumsa varieties was found to be the best-combined treatment to improve the yield of the crop in the study area. The results of the study indicated the need to ameliorate soil acidity and select acid-tolerant faba bean varieties for enhancing the yield of the crop.